Pembangunan Sistem Informasi Pengajuan Kegiatan dan Pemberian Poin Bagi Mahasiswa Fakultas Ilmu Komputer Universitas Brawijaya - Auliaur Rasyid; Fajar Pradana; Denny Sagita Rusdianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Faculty of Computer Science (FILKOM) Universitas Brawijaya has several student organizations. In proposing activities or events, the organization may request permission or financial assistance from the faculty by submitting a proposal of activities. However, based on interview the author to the FILKOM student affairs there are problems that faced by the student affairs or student. Student affairs problems are the writing errors or the format of the student proposal, the student is unaware of proposal procedure, the files collected by the student are incomplete, and many students who ask the current proposal stage. Whereas for the students, the stage of the submission of activities is too long and if there are some staff are not present or cannot be found, will increase the time required to propose activities. To overcame these problems the authors offer research to implement Information System Development on Activity Proposal and assessment for Students Faculty of Computer Science Brawijaya University with Laravel framework. The assessments are designed using the Student Credit Unit (SKM) FILKOM. The information system of this activity proposal has been successfully tested by using white box testing method on unit test with result of average complexity is 3. The result of this research revealed that there is low logic complexity. Whereas using black box testing on validation test, the result is 100% valid for all testing cases.